Value of patch tests in clindamycin-related drug eruptions - Pereira, N (2011)
Background. Patch tests help to confirm the aetiology of the cutaneous adverse drug reactions involving delayed hypersensitivity mechanisms, but the results vary with the pattern of skin reaction and the culprit drug. Objectives. To analyse the results of patch tests in patients with cutaneous adverse drug reactions imputable to clindamycin and assess their contribution to the diagnosis. Patients and methods. Between 2005 and 2009, we studied patients with delayed cutaneous adverse drug reactions following administration of clindamycin, usually associated with other drugs. After resolution of the cutaneous adverse drug reaction, patch tests were performed with a series of antibiotics, including pure clindamycin 10% in petrolatum. Results. We studied 30 patients (23 females and 7 males) aged 33-86 years (mean 59.97 years) with generalized maculopapular exanthema where clindamycin was among the highly suspected drugs. Two patients had a previous positive involuntary rechallenge. Patch tests with clindamycin were positive in 9 of 30 patients (30%). More than 50 control patients patch tested with clindamycin were negative. Discussion. We considered the positive patch tests results with clindamycin, in the 9 patients with maculopapular exantema, to be specific, versus the negative results observed in the control group. Although the sensitivity is low (30%), they confirmed the responsibility of this antibiotic in cutaneous adverse drug reactions in which, with only chronological criteria, it was not possible to conclude on the culprit drug.